THE IMPORTANCE OF PHYSICAL TRAINING FOR DIFFERENT PROFESSIONALS (Archive of Conferences, 2021)
The progressive rhythm of our life requires more and more physical activity and preparedness from us. The increasing loads that fall on our shoulders throughout life require a higher physical perfection, which must be achieved through physical education